Recalcitrant Emotions: A Phenomenological View - Laasik, Kristjan (Problemos, 2020)
In this paper, I sketch an account of emotion that is based on a close analogy with a Husserlian account of perception. I also make use of the approach that I have limned, viz., to articulate a view of the kind of “conflict without contradiction” (CWC) which may obtain between a recalcitrant emotion and a judgment. My main contention is that CWC can be accounted for by appeal to the rationality of perception and emotion, conceived as responsiveness to experiential evidence. The conflicts in question can be regarded as obtaining between different strands of evidence, and our perceptual and emotional experiences can be thus conflicted even among themselves, not only in the special case of a conflict with a judgment.